Pharmacokinetics, Bioavailability, Excretion and Metabolism Studies of Akebia Saponin D in Rats: Causes of the Ultra-Low Oral Bioavailability and Metabolic Pathway - Li, Pengfei; Peng, Jun; Li, Yuexin; Gong, Lili; Lv, Yali; Liu, He; Zhang, Tianhong; Yang, Song; Liu, Hongchuan; Li, Jinglai; Liu, Lihong (Frontiers in Pharmacology, 2021)
Background: Akebia saponin D (ASD) has a variety of biological activities and great medicinal potential, but its oral bioavailability is too low to limit its development. Its pharmacokinetic profiles and excretion and metabolism in vivo have not been fully elucidated. This study intends to further study in this area. Methods: A simple LC-MS/MS method used to simultaneous quantify ASD and its metabolites M1 M5 in rat plasma, feces, urine and bile was established with negative ESI model using dexketoprofen as internal standard. Meanwhile, UPLC-HR/MS system was used to screen all possible metabolites in urine, feces and bile, and compared with blank samples collected before administration. Results: The AUC0-t values after intravenous administration of 10 mg/kg and intragastrical administration of 100 mg/kg ASD were 19,055±8,642 h*ng/mL and 47.16±29.64 h*ng/mL, the oral bioavailability was determined to be extremely low (0.02%) in rats. The higher exposure of M4 and M5 than M0 in terminal phase of plasma concentration time profile, ASD was stable in rat liver microsome incubation system, suggesting the low bioavailability of ASD might be attributing to the poor gastrointestinal permeability and extensive pre-absorption degradation rather than potent first pass metabolism. This postulation was further verified by series intervention studies, improving lipid solubility, intestinal permeability and inhibition of intestinal flora can increased the relative bioavailability more than 4-5 times. After intravenous administration, the cumulative excretion rates of ASD in urine and bile were 14.79 ± 1.87% and 21.76 ± 17.61%, and only 0.011% in feces, suggesting that urine and bile were the main excretion pathways and there were lots of biotransformation in gastrointestinal tract. 15 kinds of ASD metabolites were observed in urine, feces and bile. The main metabolites were ASD deglycosylation, demethylation, dehydroxylation, decarbonylation, decarboxylation, hydroxylation, hydroxymethylation, hydroxyethylation and hydrolysis. Conclusion: The pharmacokinetics, bioavailability, metabolism and excretion of ASD in rats were systematically evaluated for the first time in this study. It has confirmed that the ultra-low oral bioavailability is due to poor gastrointestinal permeability, extensive pre-absorption degradation and biotransformation. Urine and bile are the main excretion pathways of ASD. The metabolic pathway was identified to further clarify the metabolism.